2017
DOI: 10.1016/j.bbadis.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

SOX2 function and Hedgehog signaling pathway are co-conspirators in promoting androgen independent prostate cancer

Abstract: Developmentally inclined hedgehog (HH) signaling pathway and pluripotency inducing transcription factor SOX2 have been known to work syngerstically during cellular reprogramming events to facilitate efficient differentiation. Hence, it is not surprising that both the factors are actively involved in arbitrating malignant growth, including prostate cancer progression. Here, we have described in details the potential mechanisms by which SOX2 effects neoplastic characteristics in prostate cancer and investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 49 publications
1
12
1
Order By: Relevance
“…Here we found that OKC expresses SOX2 and BCL-2 proteins in a significant manner, but with no statistical correlation between them. Nevertheless, it is plausible to assume that their expression in OKC is not just a coincidence, since both are related to the Hh signaling pathway (35,39,40) and both seem to be influenced by miR-15a (24,41). Our findings are in sync with those of other studies that also found SOX2 and BCL-2 expression in OKC (9,18).…”
Section: Discussionsupporting
confidence: 89%
“…Here we found that OKC expresses SOX2 and BCL-2 proteins in a significant manner, but with no statistical correlation between them. Nevertheless, it is plausible to assume that their expression in OKC is not just a coincidence, since both are related to the Hh signaling pathway (35,39,40) and both seem to be influenced by miR-15a (24,41). Our findings are in sync with those of other studies that also found SOX2 and BCL-2 expression in OKC (9,18).…”
Section: Discussionsupporting
confidence: 89%
“…It is possible that more than 1 signaling pathway is active in a particular cancer; therefore, simultaneously targeting these pathways may help prevent or postpone the development of resistance. For example, in vitro in prostate cancer cells, inhibition of HH and Sox2 signaling concomitantly led to reduced metastatic behavior, survival capacity and invasiveness, and increased apoptosis [90]. In a mouse model of medulloblastoma, blocking mammalian target of rapamycin (mTOR) and HH signaling prevented HHI resistance [86].…”
Section: The Role Of Multiple Signaling Pathwaysmentioning
confidence: 99%
“…Furthermore, mutations in TP53 and RB1 tumor suppressor genes can promote a cellular plasticity state mediated by increased expression of SOX2 that, when it is compromised with antiandrogen therapy promotes resistance through lineage switching [ 62 ••]. It has also recently been shown that the Hedgehog (HH) signaling pathway and SOX2 co-operate in androgen-independent prostate cancer to promote carcinogenesis [ 146 ].…”
Section: Oncogenic Pathways Involved In Epigenetic Regulationsmentioning
confidence: 99%